PENGARUH MEDIA AUDIO VISUAL BERBASIS MODEL INQUIRY TERHADAP PEMAHAMAN MATERI BESSRWIRAUSAHA DALAM PEMBELAJARAN BAHASA INDONESIA PADA SISWA KELAS 5 SDN 76 TAROWANG - Asratul Muarif Arif; Nurul Magfirah Nurfurqon; Besse Syukroni Baso; Haris (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to examine the extent to which the use of audio-visual media combined with the inquiry model can help students understand entrepreneurship material in Indonesian language lessons for fifth-grade students at SDN 76 Tarowang. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, carried out in two cycles. Each cycle consisted of planning, implementation, observation, and reflection. The subjects of this study were 26 fifth- grade students. Data were collected through observation, interviews, and learning achievement tests, then analyzed descriptively and with a paired sample t-test. The findings showed improvements in both student activity and learning outcomes. In the first cycle, some students were still passive, but in the second cycle they became more active in asking questions, expressing opinions, and participating in discussions. The average score also increased, from 81.86 in the pretest to 87.04 in the posttest. Statistical testing indicated a significance value of 0.002 < 0.05, which means there was a significant difference between the results before and after the action.Overall, the use of audio-visual media with the inquiry approach proved effective in enhancing students’ understanding of entrepreneurship material, while also encouraging them to be more active in the learning process.